2003
DOI: 10.1002/ejoc.200210611
|View full text |Cite
|
Sign up to set email alerts
|

Nitration of Heteroaryltrimethyltins by Tetranitromethane and Dinitrogen Tetroxide: Mechanistic Aspects, Scope and Limitations

Abstract: The nitration of 2‐(trimethylstannyl)heteroarenes by tetranitromethane (TNM) or dinitrogen tetroxide has been shown to be possible when the HOMO energy of the heteroaryltin is high enough to allow the formation of the corresponding radical cation. The reaction proceeds through a charge‐transfer complex between heteroaryltin and TNM, followed by a single‐electron transfer, which is enhanced under sunlamp irradiation. Accordingly, 2‐nitrobenzo[b]furan, 2‐nitrobenzo[b]thiophene, 2‐nitropyridine and 2‐nitroindoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Tetranitromethane ͑TNM͒ can be used as a reagent for photonitration, for example, in syntheses of high-energy materials 91 or the heterocyclization of alkenes. 92 Early infrared 93 and electron gas diffraction studies 94,95 showed the structure of TNM to possess S 4 point group symmetry.…”
Section: Larger Systems †C"no 2 … 4 and Adamantane ‡mentioning
confidence: 99%
“…Tetranitromethane ͑TNM͒ can be used as a reagent for photonitration, for example, in syntheses of high-energy materials 91 or the heterocyclization of alkenes. 92 Early infrared 93 and electron gas diffraction studies 94,95 showed the structure of TNM to possess S 4 point group symmetry.…”
Section: Larger Systems †C"no 2 … 4 and Adamantane ‡mentioning
confidence: 99%
“…Ligand 6 was readily prepared by Stille [14] reaction of 3-bromodibenzothiophene S,S-dioxide 4 [15] with commercially available 2-tris(n-butyl)stannylpyridine (5) [16] in moderate yield (58 %). An excess of ligand 6 was then treated with Ir(acac) 3 in glycerol at 220°C [17] to give the fac-triscyclometalated iridium(III) complex 3 in 82 % yield.…”
Section: Synthesismentioning
confidence: 99%
“…[37][38][39][40][41] Unusable complex mixtures of products were obtained from the attempted reactions of n-Bu 3 SnLi with cyanuric chloride or 2,4-dichloro-6-phenoxy-1,3,5-triazine in various conditions. [42] In particular, the formation of n-Bu 3 SnCN was identified by GC/MS. Interaction of cyanuric tribromide 119 with hexamethyl ditin in the presence of a catalytic amount of Pd 0 in benzene media in a sealed tube at 150 C was also investigated (Scheme 25).…”
Section: S C H E M E 1 0 Magnesiation Zincation and Couplings Of Fumentioning
confidence: 99%
“…Interaction of cyanuric tribromide 119 with hexamethyl ditin in the presence of a catalytic amount of Pd 0 in benzene media in a sealed tube at 150 C was also investigated (Scheme 25). [42] This process resulted in formation of a mixture of products of free-radical insertion and self-fragmentation, among which stannyl-, methyl-, and cyanosubstituted 1,3,5-triazines 120 to 124 were identified (Scheme 25).…”
Section: S C H E M E 1 0 Magnesiation Zincation and Couplings Of Fumentioning
confidence: 99%